SINERGI ANTARA KEINDAHAN ALAM DAN PARIWISATA BERBASIS KOMUNITAS PADA PAKET WISATA DESA PLAGA, BADUNG - Retno Juwita Sari; Ni Wayan Kurnia Sari; Swyti Fandalista Silly; Ida Ayu Etsa Pracintya; I Wayan Putra Aditya (Fakultas Teknik dan Informatika Universitas PGRI Mahadewa Indonesia, 2025)
Pelaga Village, located in Badung Regency, Bali, is known for its natural beauty and diverse agricultural products, making it an ideal destination for tourists seeking tranquility and an experience close to nature. The village has cool air and lush green landscapes, as well as superior agricultural commodities such as asparagus, coffee, and organic vegetables. Pelaga Village faces challenges in managing sustainable tourism, including a lack of community understanding of the importance of environmentally friendly tourism. In an effort to increase tourism potential, a three-day, two-night educational and adventure-based tour package was designed, which includes a climb to Puncak Mangu Temple, a visit to an asparagus garden to learn about sustainable agriculture, and trekking to Nungnung Waterfall. This package aims to provide an immersive experience for tourists, while empowering local communities through active participation in tourism management. Through a holistic and sustainable approach, it is hoped that this tour package will not only attract tourists, but also have a positive impact on the community and the environment. By involving the community as guides and service providers, this program is expected to improve the economic welfare of the village, environmental conservation, and education for tourists about local culture and agriculture. These results are expected to be a model for other villages in developing sustainable and community-based tourism.